2020
DOI: 10.1136/bmj.l6911
|View full text |Cite|
|
Sign up to set email alerts
|

How can we realise the full potential of health systems for nutrition?

Abstract: Poor nutrition contributes substantially to global disease, diminishing the wellbeing of women and children in low and middle income countries, and better nutrition must be part of the universal health coverage agenda, say Rebecca Heidkamp and colleagues

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 12 publications
1
51
0
Order By: Relevance
“…Investing in data systems can help to close gaps in the data available to analyse coverage and opportunity gaps. 4 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Investing in data systems can help to close gaps in the data available to analyse coverage and opportunity gaps. 4 …”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Our findings are aligned with evidence from analyses of 50 countries showing that global movements to scale BMJ Global Health up effective nutrition interventions and achieve universal health coverage have not been connected to reach their full potential. 4 Overall review of 36 studies also showed large gaps between contact coverage and quality-adjusted coverage levels (10-38 pp) across the continuum of care for reproductive, maternal, newborn and child health. 27 Therefore, closing the opportunity gap by increasing nutrition intervention coverage among those already reached by other platforms should be an immediate priority.…”
Section: Opportunity Gaps By Statesmentioning
confidence: 99%
See 3 more Smart Citations